Marketingowe strategie rewitalizacji miejskiej w Polsce - próba typologii - Obrębalski, Marek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Today we can observe different crisis situations both in spatial-functional and in socio-economic sphere of many towns. It extort a necessity of their revitalisation.Revitalisation programs were leaded in tens towns in Poland, most often in old-town areas, in central town's quarters from XIX and early XX century, in post-industrial and post-military areas. Different strategies of urban revitalisation were implemented in practice. Their aims, range of activities, level of participation of inhabitants and location of area of revitalization changes are the most important criteria that differentiate these strategies. It allows to multicriterial classification of marketing strategies of urban revitalization. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 699-706